La autonomía indígena frente a los deberes primordiales del estado vulnera su seguridad jurídica. - Fuentes Almache, Marcelo Jonathan (2024)
The present study aims to analyze the legal pertinence for reforming the Public Security and State Law, for regulating the security in indigenous territories, and therefore to allow the realization of military activities in cases of extreme threats to the security and respect of fundamental rights of these indigenous communities. For this purpose, an introductory part was carried out in which there are established the backgrounds , current situation and justification of the problem to study; regarding the methodology, the methods techniques and instruments were settled for establishing the foundations to develop this research, for which a survey was designed and carried out to 30 professionals in the legal area, and also including an interview to 3 Judges; the main results obtained through the survey showed that 66.70% of the surveyed population considered that the limitation for military activity in indigenous territories leads to insecurity; additionally, the documental analysis evidenced that the presence of regular or irregular armed groups in indigenous territory caused forced displacements; similarly the interview’s results also showed that, as it is established, the State must provide protection and security to indigenous communities, but also respect their autonomy, given that it is the indigenous authorities who can authorize the access of military activities in their territories. The discussion provided a contrast with other research done on this topic, and finally the conclusions were presented.